Pengaruh Beban Kerja, Gaya Kepemimpinan, dan Lingkungan Kerja Terhadap Stress Kerja (Studi Terhadap Kantor Akuntan Publik (KAP) Mirawati Sensi Idris) - Yudho Yuanto; Syaiful Anwar (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
This research aims to examine the influence of workload (X1), leadership style (X2) and work environment (X3) on work stress (Y). Sampling in this study used a saturated sampling technique with a total of 55 respondents including employees of KAP Mirawati Sensi Idris. The analysis method used is the path analysis method with the help of SPSS V.22 software. The results of this research show that the Workload variable (X1) (0.011) has a significant effect on Work Stress (Y), the Leadership Style variable (X2) (0.013) has a significant effect on Work Stress (Y), the Work Environment variable (X3) (0.551 ) has no significant effect on Job Stress (Y). The results of this research show that Workload and Leadership Style have a significant effect and the Work Environment does not have a significant effect on Work Stress in Employees of KAP Mirawati Sensi Idris